2018
DOI: 10.1101/305185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivo Chemical Reprogramming of Astrocytes into Functional Neurons

Abstract: Mammals lack robust regenerative abilities. Lost cells in impaired tissue could potentially be compensated by converting nearby cells in situ through in vivo reprogramming. Small molecule-induced reprogramming is a spatiotemporally flexible and non-integrative strategy for altering cell fate, which is, in principle, favorable for the in vivo reprogramming in organs with poor regenerative abilities, such as the brain. Here, we demonstrate that in the adult mouse brain, small molecules can reprogram resident ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Unfortunately, so far, in vivo studies to induce chemical transdifferentiation accomplished only with small molecules resulted either in promoting only an increase in adult brain neurogenesis [ 73 ] or reprogramming of mouse astrocytes into scattered functional mature neurons with electrophysiological characteristics and integration with resident neurons in the brain [ 74 ]. In complex, current in vivo studies although appealing are still superficial and limited to confirm reprogrammed cell capabilities, cell survival and integration and a more extensive testing in animal models is necessary before finding a clinical application.…”
Section: Commentarymentioning
confidence: 99%
“…Unfortunately, so far, in vivo studies to induce chemical transdifferentiation accomplished only with small molecules resulted either in promoting only an increase in adult brain neurogenesis [ 73 ] or reprogramming of mouse astrocytes into scattered functional mature neurons with electrophysiological characteristics and integration with resident neurons in the brain [ 74 ]. In complex, current in vivo studies although appealing are still superficial and limited to confirm reprogrammed cell capabilities, cell survival and integration and a more extensive testing in animal models is necessary before finding a clinical application.…”
Section: Commentarymentioning
confidence: 99%
“…In 2018, Deng's team released their data about in vivo transdifferentiation of neurons from mouse astrocytes with a cocktail combination consist of dbcAMP, Forskolin, ISX9, CHIR99021, I-BET151, and Y-27632 [ 78 ]. The combination of chemicals was injected into mouse brains at a stable rate for two weeks with an osmotic minipump.…”
Section: Transdifferentiation In Vivomentioning
confidence: 99%
“…Additionally, a recent preprint report of in vivo direct conversion garnered considerable attention. A study reported successfully converting resident astrocytes to functional neurons in situ in adult mouse brain[49]. Remarkably, such in situ -generated neurons acquired electrophysiological functions and could functionally interact with resident neurons in the brain.…”
Section: Direct Lineage Conversionmentioning
confidence: 99%
“…Comparatively, chemical-mediated strategy minimized the risk of genetic alteration and is easier for scalable manufacturing, stocking, and delivery[23], eventually preferable for in vivo therapeutic applications. Recently, for the first time, in vivo chemical reprogramming was reported to successfully convert the resident astrocytes into functional neurons in the adult mouse brain, resembling endogenous neurons in both neuron-specific marker expression and electrophysiological properties[49]. Meanwhile, cardiomyocytes were induced from adult cardiac fibroblasts by direct full chemical administration in vivo , and although the reprogramming efficiency is relatively low, the chemical cocktail treatment markedly decreased the scar formation and enhanced cardiac functions in myocardial infarction mice[52]; these encouraging achievements not only provide a general strategy for in vivo reprogramming but also open a novel path to regenerate the diseased organs in situ .…”
Section: Challengesmentioning
confidence: 99%